LEVEL PENERAPAN BIOSEKURITY PADA PETERNAKAN BABI SKALA BESAR DI DESA NOELBAKI, KECAMATAN KUPANG TENGAH KABUPATEN KUPANG - Petrus Malo Bulu; Yanse Y. Rumlaklak; Erda E. R. Hau; Jois M. Jacob (Partner, 2013)
Level of Biosecurity Application on Big Scale Piggery in Noelbaki village, Central Kupang sub distiric, Kupang distric. Classical Swine fever is one of swine diseases that often occurs in East Nusa Tenggara and is recognised as an endemic disease in Timor Island. This disease is also known as Hog cholera since it gained entry in the island of Timor in 1997 and has caused economic losses, which is believed as a result of low level of biosecurity application on farms. This research was aimed to identify level of application of biosecurity on farm level. Purposive sampling was our sampling method used, where all commercial pig farms in Noelbaki village involved in the survey. The research results showed that there were some variables of biosecurity applied in low level courses such as closed to small scale pig farms, use of wheel bath for trucks at the entrance of the farm and desinfection of trucks. Some biosecurity parameters had low scores, thus, it affected the low level of biosecurity.Keywords: Biosecurity, Piggery